Mitochondrial genome of the freshwater annelid Manayunkia occidentalis (Sabellida: Fabriciidae). Issue 3 (2nd July 2020) - Tilic, Ekin; Atkinson, Stephen D.; Rouse, Greg W.
Abstract: Here, we report the 15, 103 bp mitochondrial genome of the freshwater fabriciid tubeworm Manayunkia occidentalis . We recovered 13 protein-coding genes, 2 rRNA, and 22 tRNA. The gene order is consistent with the conserved pattern observed in most annelids.